Youth Psychology and Identity Transformation: The Role of Education in the novel Bumi Manusia - Ritonga, Ridwan; Kurniawan, Raden Muhammad Ardiansyah; Bachrun, Nitis Asmara; Nafiah, Rofiatun (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
This article investigates the dynamics of youth psychology and identity transformation reflected in Pramoedya Ananta Toer's Bumi Manusia, with an emphasis on the role of education as a crucial variable in character building and self-understanding. Through the character of Minke, the author examines the internal and external conflicts faced by the younger generation in the context of colonialism, as well as how education functions as an instrument to achieve social awareness and a more complex identity. The research method applied in this article is qualitative analysis with sociological and psychological approaches. Data were obtained through an in-depth reading of the novel's text, accompanied by a study of relevant literature to support the analysis. This approach allows the researcher to explore the deeper meaning and context of Minke's experiences and connect the themes of education and identity to the social reality of the time. The results of the analysis show that education does not only functions as a means of transferring knowledge but also as a transformation process that encourages youth to explore cultural values and search for identity amid social challenges. This article is expected to provide new insights into the relevance of education in shaping the identity of the younger generation in the context of Indonesian history and culture.